Effects of inactivated Parapoxvirus ovis on polymorphonuclear leukocyte function and myeloperoxidase activity in horses - (:unkn) unknown (CZECH ACADEMY AGRICULTURAL SCIENCES, 2014)
Immunomodulatory products have been used for years in veterinary medicine. Inactivated Parapoxvirus ovis (iPPVO) is currently used in equine medicine as an immunomodulator to improve the immune system and as a prophylactic treatment to prevent or treat infectious diseases. This study was designed to determine the effects of iPPVO on polymorphonuclear leukocyte (PMNL) function (phagocytosis and intracellular killing activity) and the myeloperoxidase (MPO) activity of PMNLs in horses. Twenty-four healthy English thoroughbred horses with an average age of 11 years were included in the study. Venous blood samples (10 ml) were taken before (agent-free controls) and after the administration of iPPVO (2 ml i.m. injection on Days 1, 3, and 5). PMNLs (1 x 107 cells/ml) were isolated from venous blood containing EDTA (0.1 g/ml) with Ficoll-Hypaque gradient centrifugation. Cellular phagocytosis and intracellular killing activities were assayed using a modification of Alexander's method before and after treatment with iPPVO. MPO activity was also measured. The administration of iPPVO significantly increased the phagocytic, intracellular killing, and MPO activities of equine PMNLs (P = 0.0058, P = 0.0050, and P = 0.0070, respectively). This study demonstrates a strong correlation between MPO activity and PMNL function. The administration of iPPVO to horses has a supportive effect on their cellular immunity and an immunomodulatory effect against equine viral infections.
Keywords: equine; inactivated Parapoxvirus ovis; phagocytosis; intracellular killing activity; myeloperoxidase; RESPIRATORY-DISEASE; VIRUS